2021
DOI: 10.1007/s00418-020-01950-1
|View full text |Cite
|
Sign up to set email alerts
|

Lung epithelial endoplasmic reticulum and mitochondrial 3D ultrastructure: a new frontier in lung diseases

Abstract: It has long been appreciated that the endoplasmic reticulum (ER) and mitochondria, organelles important for regular cell function and survival, also play key roles in pathogenesis of various lung diseases, including asthma, fibrosis, and infections. Alterations in processes regulated within these organelles, including but not limited to protein folding in the ER and oxidative phosphorylation in the mitochondria, are important in disease pathogenesis. In recent years it has also become increasingly apparent tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…Temporal distribution studies identified increased hnRNPA1-NP co-localization in the nuclear and mitochondrial compartments in NPtransfected and IAV-infected cells, thereby enhancing the possibility of interaction between the two. Mitochondrial accumulation of Influenza A vRNP is well documented as it is associated with the induction of interferon (IFN) and antiviral immune signaling [46][47][48][49][50]. On the other hand, hnRNPA1 is enriched in the nuclear and cytosolic fraction in response to various internal and external stimuli [51].…”
Section: Discussionmentioning
confidence: 99%
“…Temporal distribution studies identified increased hnRNPA1-NP co-localization in the nuclear and mitochondrial compartments in NPtransfected and IAV-infected cells, thereby enhancing the possibility of interaction between the two. Mitochondrial accumulation of Influenza A vRNP is well documented as it is associated with the induction of interferon (IFN) and antiviral immune signaling [46][47][48][49][50]. On the other hand, hnRNPA1 is enriched in the nuclear and cytosolic fraction in response to various internal and external stimuli [51].…”
Section: Discussionmentioning
confidence: 99%
“…While TEM has the limitation of relying on static observations, it enables distinguishing between contiguous membranes and accurate quantification of mitochondrial morphology and interactions ( Picard et al, 2013 ). One of the most recognized of these mitochondrial interactions is with the ER within different cell types ( Csordás et al, 2006 ), including epithelial cells in the context of lung diseases [reviewed in ( Bruno and Anathy, 2021 )] and immune cells [reviewed in ( Angajala et al, 2018 )]. For example, in T cells, such interaction enables metabolic reprogramming necessary for immune responses ( Bantug et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For many years, Charavarymath and colleagues have been studying the mechanisms underlying pulmonary effects of exposure to airborne organic dusts (Bhat et al 2019;Charavarymath et al 2005Charavarymath et al , 2008Charavarymath and Singh 2006). They have now focussed their attention on mitochondria (Bhat et al 2021), and provide an extensive and detailed analysis of mitochondrial structure and function in cells treated with organic dust extract (ODE). Using cultured human monocytic cells (THP1) as an in vitro model representing human lung macrophages, they performed a wide variety of mitochondrial ultrastructural and physiological analyses, including cell viability and the MTT assay, mitochondrial DNA isolation, quantitative RT-PCR, Western blot analysis, mitochondrial activity via the MitoSOX assay, calcium influx measurements, nitric oxide secretion via the Griess assay, multi-cytokine identification, subcellular fractionation, and transmission electron microscopy followed by morphological image analysis.…”
Section: The Mighty Mitochondrionmentioning
confidence: 99%
“…tOS-NPs were prepared in 100 and 1000 nm size distributions, and then conjugated to either rhodamine B or fluorescein isothiocyanate (FITC). Animals were then administered intravaginally either size of the fluorescently tagged From Bhat et al (2021) tOS-NPs, or as a combination of the two different-sized particles. The distribution of the fluorescence signal was then determined in different areas of the genital tract, including the vagina, endometrium, and ovaries.…”
Section: Thiol-organosilica Nanoparticles As a Potential Drug Delivery System For The Female Genital Tractmentioning
confidence: 99%
See 1 more Smart Citation